"Från det omedvetnas scen till Historiens scen" - Hélène Cixous och teatern - Munck , Kerstin (Tidskrift för genusvetenskap, 1997)
This a r t i d e deals with Hélene Cixous’s relation to t h e theatre. Her first play, La Pupille (1972), isn’t p e r f o r m e d so far. Her breakthrough as a playwright was Portrait de Dora (1976), where Freud’s case study is called in question by Cixous’s text and Simone Benmussa’s production. In a feminist theatrical manifesto Cixous declares theatre for h e r to be "a political gesture, with a view to changing", i.e. "the position of victim" of women in western theatre. (I.e Monde, April 28, 1977). Her opera Le nom d’Oedipe (1978), however, has been criticized for the static role of Iocaste (Kolk, 1990). Cixous describes her development as a writer as a way f r o m "the staging of the unconscious to the staging of History", and indeed her great historical plays, Sihanouk (1985) and LTndiade ( 1987), produced by Ariane Mnouchkine & T h é å t r e du Soleil, have proved her ability for the theatre. But Cixous has not remained exclusively a playwright for t h e "Stage of History", as the play On ne part pas, on ne revient pas (1991) shows. In this a r t i d e it is a r g u e d that Cixous’ early interest in body & text, as it came about in "The Laugh of t h e Medusa" and La jeune née ( b o t h in 1975) as well as in her "fictions" in the 1970’s happily goes together with her work for the theatre, the medium which works through the living body. A distinguishing quality of Cixous’s "fictions" (after 1975 she no longer calls t h em "novels") is h e r advanced linguistic play o n the signifier, which highlights the patriarchal power over language, tlius she is challenging the predominant order. For example, she writes "måle élevée" (instead of "mal élevée"), signifymg an "ill-bred girl", thus summing up the whole debate on gender as a social construction within ’Taccent circonflexe"! In working with the theatre Cixous finds o t h e r possibilities to reveal power, lies a n d stereotypes, especially in working on contradictions p r o d u c e d by a confusing inter- play body / voice / image. In Portrait de Dora even a filmed sequence is projected to counter-act t h e f r e u d i a n interpretation of Dora produced on stage. In her plays as well as in h e r "fictions" Cixous thus urges us to take an active role, as spectators and readers, in the construction of "truth".